Understanding Factors Related with Cheating in Sport: What We Know and what is Worth Future Consideration - Beatričė Sipavičiūtė; Saulius Šukys (Lithuanian Sports University, 2020)
Background. Over the past decade, there has been an increase in scholars' attention to moral behaviour in sport. Recently more studies have been dealing with cheating with a special focus on doping. The aim of this study was to provide an overview of research focusing on cheating in sport. Specifically, the purpose was to critically analyse research on personal and social factors which have been associated with an intension to cheat and cheating behaviour. Methods. Scientific research analysis on social environment factors related with cheating was carried out by focusing on personal and social environmental factors related with athletes' attitudes towards, intention and cheating behaviours. Results. Moral identity is an important factor for cheating in sport and intention to use doping. A negative relation was found between moral values of athletes and doping likelihood. Also, when athletes perceive their goal only as winning the game (goal-oriented rather than task-oriented), they are more likely to cheat. Furthermore, recent studies have found the relationship between the Dark Triad (Machiavellianism, narcissism, and psychopathy) and the use of doping in sport. Moreover, perfectionism involves positive attitudes towards doping and actual use of doping. Also, there is evidence that moral values relate with athletes' cheating and gamesmanship. Some social environment factors related with motivational climate created by the coach and parents. Coaches and parents created an ego-oriented climate associated with young athletes' positive attitudes towards cheating. Conclusion. Athlete's intention to cheat or actual behaviour is determined by both athlete's personality and social environment context. The article also provides considerations of directions for future research with special attention to cultural differences. Keywords: cheating, doping, moral identity, motivational climate, personality traits.